Tax policies supporting research activities of non-public research organizations: Overview and implications for Vietnam - Nguyen Quynh Anh; Nguyen Van Hieu; Le Minh Hai; Nguyen Thi Thuy Linh; Dang Thu Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
As Vietnam’s economy expands, the government policies in the field of science and technology (S&T) are adjusting gradually. These adjustments include the socialization of S&T activities to encourage businesses, groups, and individuals to participate in S&T. The policies also permit various organizations and individuals, including those from other countries, to establish and register non-public S&T institutions and carry out S&T activities in the territory of Vietnam. These non-public organizations operating in research and development (R&D) have played a significant role in the country’s overall socio-economic development and the progress of S&T. Recognizing their importance, it’s essential to have policies that support and enhance the R&D activities of these institutions, aligning with their role in the country’s growth. This article examines the gaps in tax policies affecting the support for R&D activities in non-public organizations in Vietnam. It proposes solutions by analyzing these gaps and referring to effective international policies that support R&D activities in non-public organizations. Code: 24011801